Kidney transplantation after rescue allocation—meticulous selection yields the chance for excellent outcome. Issue 3 (26th December 2020) - Assfalg, Volker; Misselwitz, Svea; Renders, Lutz; Hüser, Norbert; Novotny, Alexander; Jäger, Carsten; Büttner-Herold, Maike; Amann, Kerstin; Schmaderer, Christoph; Heemann, Uwe; Wen, Ming; Haberfellner, Flora; et al.
Abstract: Background: The small number of organ donors forces transplant centres to consider potentially suboptimal kidneys for transplantation. Eurotransplant established an algorithm for rescue allocation (RA) of kidneys repeatedly declined or not allocated within 5 h after procurement. Data on the outcomes and benefits of RA are scarce to date. Methods: We conducted a retrospective 8-year analysis of transplant outcomes of RA offers based on our in-house criteria catalogue for acceptance and decline of organs and potential recipients. Results: RA donors and recipients were both older compared with standard allocation (SA). RA donors more frequently had a history of hypertension, diabetes or fulfilled expanded criteria donor key parameters. RA recipients had poorer human leucocyte antigen (HLA) matches and longer cold ischaemia times (CITs). However, waiting time was shorter and delayed graft function, primary non-function and biopsy-proven rejections were comparable to SA. Five-year graft and patient survival after RA were similar to SA. In multivariate models accounting for confounding factors, graft survival and mortality after RA and SA were comparable as well. Conclusions: Facing relevant comorbidities and rapid deterioration with the risk of being removed from the waiting list, kidney transplantation after RA was identified to allow for earlier transplantation with excellent outcome. Data from this survey propose not to reject categorically organs from multimorbid donors with older age and a history of hypertension or diabetes to aim for the best possible HLA matching and to carefully calculate overall expected CIT.